Timing of high-frequency cortical stimulation in a genetic absence model. (2nd June 2016) - van Heukelum, S.; Kelderhuis, J.; Janssen, P.; van Luijtelaar, G.; Lüttjohann, A.
Highlights: Timing of high-frequency stimulation (HFS) determines acute and long-term effects. Cortical closed-loop HFS reliably disrupts SWD. Cortical closed-loop HFS reduces SWD number during and after stimulation. Yoked stimulation of cortex can induce epileptic afterdischarges. Abstract: Introduction: Seizure control is one of the ultimate aims of epileptology: here acute and prolonged effects of closed loop high-frequency stimulation of the somatosensory cortex on the expression of spontaneously occurring spike-wave discharges (SWD) were investigated in a genetic absence model. Effects of closed loop stimulation in the experimental group were compared with a yoked control group allowing to investigate the effect of timing related to SWD occurrence, while controlling for amount and intensity of stimulation. Methods: WAG/Rij rats were implanted with stimulation electrodes in the deep layers of the somatosensory cortex, and recording electrodes in the cortex and thalamus. Closed-loop and yoked stimulation (1 sec trains, biphasic 0.4 msec pulses, 130 Hz) sessions lasted 24 h. The stimulation sessions were preceded and followed by baseline and post stimulation 24-h recordings. Results: Closed-loop stimulation interrupted SWD and duration of SWD was shortened. Both types of stimulation resulted in a reduction in SWD number during stimulation sessions. Closed-loop stimulation also resulted in less SWD during the last eight hours of the post-stimulation recording session. Sometimes yoked stimulation induced low-frequency afterdischarges. Discussion: SWD can be aborted by closed-loop stimulation of the somatosensory cortex, and at the same time the number of SWD was reduced. It can be regarded as a relatively safe neuromodulatory technique without habituation. The reduction of SWD during yoked stimulation session might be caused by 3 Hz afterdischarges. The reduction of SWD on the stimulation and post-stimulation sessions demonstrates the critical relevance of timing for the induction of longer lasting neuromodulatory effects: it suggests that absence seizures themselves might be involved in their reoccurrence.